High preoperative blood oxaloacetate and 2-aminoadipic acid levels are associated with postoperative delayed neurocognitive recovery - Mao, Haoli; Huang, Huimin; Zhou, Ren; Zhu, Jiao; Yan, Jia; Jiang, Hong; Zhang, Lei (Frontiers in Endocrinology, 2023)
Introduction This study aimed to identify preoperative blood biomarkers related to development of delayed neurocognitive recovery (dNCR) following surgery. Methods A total of 67 patients (≥65 years old) who underwent head and neck tumor resection under general anesthesia were assessed using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). Preoperative serum metabolomics were determined using widely targeted metabolomics technology. Results Of the 67 patients, 25 developed dNCR and were matched to 25 randomly selected patients from the remaining 42 without dNCR. Differential metabolites were selected using the criteria of variable importance in projection > 1.0 in orthogonal partial least squares discrimination analysis, false discovery rate <0.05, and fold-change >1.2 or <0.83 to minimize false positives. Preoperative serum levels of oxaloacetate (OR: 1.054, 95% CI: 1.027–1.095, P = 0.001) and 2-aminoadipic acid (2-AAA) (OR: 1.181, 95% CI: 1.087–1.334, P = 0.001) were associated with postoperative dNCR after adjusting for anesthesia duration, education, and age. Areas under the curve for oxaloacetate and 2-AAA were 0.86 (sensitivity: 0.84, specificity: 0.88) and 0.86 (sensitivity: 0.84, specificity: 0.84), respectively. High levels of preoperative oxaloacetate and 2-AAA also were associated with postoperative decreased MoCA (β: 0.022, 95% CI: 0.005–0.04, P = 0.013 for oxaloacetate; β: 0.077, 95%CI: 0.016–0.137, P = 0.014 for 2-AAA) and MMSE (β: 0.024, 95% CI: 0.009–0.039, P = 0.002 for oxaloacetate; β: 0.083, 95% CI: 0.032–0.135, P = 0.002 for 2-AAA) scores after adjusting for age, education level, and operation time. Conclusion High preoperative blood levels of oxaloacetate and 2-AAA were associated with increased risk of postoperative dNCR. Clinical trial registration https://classic.clinicaltrials.gov/ct2/show/NCT05105451, identifier NCT05105451.